FIGURE 5 in A new species of Sphaerodoridium Lützen, 1961 from Iceland (Polychaeta: Sphaerodoridae) - Moreira, Juan; Parapar, Julio (Zenodo, 2015)
FIGURE 5. SEM micrographs of Sphaerodoridium guerritai sp. nov. A, stalked macrotubercles and dorsal papillae; B, stalked macrotubercle; C–D, midbody chaetigers, ventral view (filled white arrows pointing to nephridial papillae; non-filled arrows pointing to ventral body papillae in same transversal row; discontinuous white line marking ventral midline); E, nephridial papillae from same chaetiger; F, appearance of tegument and nephridial papilla, detail. Published as part of Moreira, Juan & Parapar, Julio, 2015, A new species of Sphaerodoridium Lützen, 1961 from Iceland (Polychaeta: Sphaerodoridae), pp. 91-105 in Zootaxa 3911 (1) on page 98, DOI:10.11646/zootaxa.3911.1.5, http://zenodo.org/record/236683